2001
DOI: 10.1086/320370
|View full text |Cite
|
Sign up to set email alerts
|

WFPC2 Images of the Central Regions of Early-Type Galaxies. I. The Data

Abstract: We present high-resolution R-band images of the central regions of 67 early-type galaxies obtained with the Wide Field and Planetary Camera 2 (WFPC2) aboard the Hubble Space T elescope (HST ). This homogeneously selected sample roughly doubles the number of early-type galaxies that have now been imaged at HST resolution and complements similar data on the central regions of radio galaxies and the bulges of spiral galaxies. Our sample strikingly conÐrms the complex morphologies of the central regions of early-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
377
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(410 citation statements)
references
References 62 publications
28
377
3
Order By: Relevance
“…Applying the Nuker model to the light profiles of 120 "core" galaxies, Lauer et al (2007a) noted that the Nuker model break radii (R b,Nuk ) are only roughly correlated with the galaxy properties. However, they identified a better correlated parameter rγ (the "cusp radius") as a measure of the core size (Carollo et al 1997a;Rest et al 2001). Dullo & Graham (2012) subsequently showed that this cusp radius closely matches the break radius of the core-Sérsic model which we employ here 2 .…”
Section: Introductionmentioning
confidence: 78%
“…Applying the Nuker model to the light profiles of 120 "core" galaxies, Lauer et al (2007a) noted that the Nuker model break radii (R b,Nuk ) are only roughly correlated with the galaxy properties. However, they identified a better correlated parameter rγ (the "cusp radius") as a measure of the core size (Carollo et al 1997a;Rest et al 2001). Dullo & Graham (2012) subsequently showed that this cusp radius closely matches the break radius of the core-Sérsic model which we employ here 2 .…”
Section: Introductionmentioning
confidence: 78%
“…galaxies (e.g., Rest et al 2001;Ravindranath et al 2001). We wish to avoid such features here, as we are presently concerned only with the bulge (and outer disk, if one exists) of M32.…”
Section: Modeling the Surface Brightness Profilementioning
confidence: 99%
“…Afterward, nuclear stellar disks (NSDs) and larger scale embedded disks were reported in a large number of early-type galaxies as a results of photometric (Lauer et al 1995;Carollo et al 1997;Ravindranath et al 2001;Rest et al 2001;Tran et al 2001;Ferrarese et al 2006;Seth et al 2006;Simões Lopes et al 2007;Kormendy et al 2009) and spectroscopic surveys (Halliday et al 2001;Kuntschner et al 2006;McDermid et al 2006) respectively. Given that nuclear disks are easiest to detect when nearly edgeon (Rix & White 1990), the observed fraction is consistent with NSDs being a common structure in early-type galaxies (Ledo et al 2010).…”
Section: Introductionmentioning
confidence: 99%